(untitled) (Indian Journal of Animal Production and Management, 2013)
A survey was conducted on 576 sheep farmers by multistage stratified random sampling technique from three different zones of Telangana region of Andhra Pradesh to study the marketing practices adopted by the sheep farmers. It was found that majority (73.44%) of sheep farmers sold their lambs between 3-6 months on physical appearance (52.45%). 40.10% of the farmers sold their animals to the middle men once in a year. Results further indicated that 90.80% of the farmers sold their animals in their own villages. In the study area the main reason for selling of sheep was urgent need of cash (60.24%) to meet domestic expenses. Marketing practices in the study area is very poor hence organized market should be developed to make the sheep enterprise more remunerative and to eliminate middle men.